The Biotechnological Potential of Tissue Culture for the Conservation and Production of Secondary Metabolites in Pimpinella pruatjan (Purwoceng): A Systematic Literature Review - Mohamad Kashuri (Green Health International Journal of Health Sciences Nursing and Nutrition, 2025)
Pimpinella pruatjan is a native Indonesian medicinal plant increasingly threatened by overexploitation and limited cultivation techniques. This study aims to systematically review the role of tissue culture in the conservation and production of its secondary metabolites. Using the Systematic Literature Review (SLR) method, data were gathered from scientific literature published in the last five years through open-access databases. The findings reveal that tissue culture techniques not only effectively regenerate purwoceng but also significantly enhance the production of bioactive compounds such as flavonoids, betaine, and sterols. This study demonstrates that biotechnology-based tissue culture is a strategic solution for conserving endangered medicinal plants while optimizing their utilization for biodiversity-based pharmaceutical industries.